The Effect of Aircraft Noise Exposure on Incidence of Hypertension in Adi Sumarmo Boyolali Airport Employees - Prasetya, Novandi Lisyam (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: The exposure of noise and vibration that exceed the threshold in quite long time will result in heart frequency and blood pressure changes. Prevalence of hypertension occurrence due to aircraft noise exposure is increasing, data mentioned that noise exposure of 50 dB or more can increase the incidence of hypertension up to 95% and noise exposure of 70 dB or more in quite long time can highly increase the incidence of hypertension. This research aimed to investigate the effect of aircraft noise exposure on hypertension incidence in Adi Sumarmo Boyolali Airport employees. Methods: This research is an observational analytic study with cross sectional approach. The samples of this research are Adi Sumarmo Boyolali Airport employees which were chosen using simple random sampling method. The apron workers were the main respondent while the non apron workers were the control. Data analysis with Chi-Square Test. Results: In low noise exposure, 9 samples (20.93%) were diagnosed with hypertension and in high noise exposure, 22 samples (51.16%) were diagnosed with hypertension. The result of Chi-Square test showed the number of significance level 0.004, so the p-value < 0.05. This result showed that this research is significant. Conclusions: There is significant effect of aircraft noise exposure on incidence of hypertension in Adi Sumarmo Boyolali airport employees. Keywords: Noise, hypertension, blood pressure, frequency, airport. Â